2021
DOI: 10.2147/ott.s287931
|View full text |Cite
|
Sign up to set email alerts
|

PDIA4 Correlates with Poor Prognosis and is a Potential Biomarker in Glioma

Abstract: Purpose: Gliomas, characterized by aggressiveness and invasiveness, remain incurable after conventional therapies. The molecular mechanisms driving the progression and maintenance of glioma are still poorly understood. Methods: The TCGA and CGGA databases were chosen for bioinformatics analysis. Gene expression profiling interactive analysis (GEPIA) was performed for differential analysis. The Kaplan-Meier method was chosen for survival analysis. Analysis of stromal and immune infiltration was performed using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The P4HB (also known as PDIA1) and PDIA4, which were chosen from the six-gene signature, belong to the protein PDI protein family and have been proved to be related to ER stress activation in human cancers (Joo et al, 2007;Kranz et al, 2017;Winship et al, 2017;Liu et al, 2019;Wang et al, 2020), especially the PERK signaling pathway (Kranz et al, 2017(Kranz et al, , 2020. Serval recent researches has pointed out that P4HB and PDIA4 correlated with the malignant progression of glioma, but these conclusions have not been sufficiently verified by in vitro experiments (Zou et al, 2018;Li et al, 2021). Besides, the P4HB and PDIA4, which have significant prognostic value in gliomas, were also the important components of the ER stress-related signature.…”
Section: Discussionmentioning
confidence: 99%
“…The P4HB (also known as PDIA1) and PDIA4, which were chosen from the six-gene signature, belong to the protein PDI protein family and have been proved to be related to ER stress activation in human cancers (Joo et al, 2007;Kranz et al, 2017;Winship et al, 2017;Liu et al, 2019;Wang et al, 2020), especially the PERK signaling pathway (Kranz et al, 2017(Kranz et al, , 2020. Serval recent researches has pointed out that P4HB and PDIA4 correlated with the malignant progression of glioma, but these conclusions have not been sufficiently verified by in vitro experiments (Zou et al, 2018;Li et al, 2021). Besides, the P4HB and PDIA4, which have significant prognostic value in gliomas, were also the important components of the ER stress-related signature.…”
Section: Discussionmentioning
confidence: 99%
“…PDI family member PDIA4 has been shown to play roles in the pathogenesis of various diseases ( 4 ). Previous studies have uncovered the overexpression and cancer-promoting activity of PDIA4 in several types of cancer ( 6 , 7 , 9 ). In the present study, the expression pattern and biological roles of PDIA4 in cervical cancer were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…PDIA4 exhibited a dramatic upregulation in docetaxel-resistant prostate cancer cells ( 9 ). Moreover, PDIA4 was an independent risk factor for disease-free survival and OS in ovarian cancer ( 29 ) and was associated with poor prognosis in patients with glioma ( 7 , 30 ). Recently, Wang et al ( 31 ) reported that PDIA4 could promote glioblastoma progression via the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, RIPK1/RIPK3 activation was proved to be correlated with the enhancement of antitumor immunity via maturated DC and CD8 + T cells in the tumor microenvironment (TME) ( Park et al, 2021 ). The necroptosis-related gene (NRG) PDIA4 was thought to be interrelated with glioma-related immune cells, such as CD8 + T cells, Tregs, and eosinophils ( Li et al, 2021 ). Previous research has proven that the mutants of isocitrate dehydrogenase 1 ( IDH1 ) can lead to necroptosis resistance by inducing hypermethylation of the RIPK3 promoter ( Yang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%